2008
DOI: 10.1016/j.memsci.2008.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Films based on chitosan polyelectrolyte complexes for skin drug delivery: Development and characterization

Abstract: a b s t r a c tNovel chitosan based polyelectrolyte complexes (PEC) were developed and optimized in order to obtain films possessing the optimal functional properties (flexibility, resistance, water vapour transmission rate and bioadhesion) to be applied on skin. The development was based on the combination of chitosan and two polyacrylic acid (PAA) polymers with different crosslinkers and crosslinking densities. The interaction between the polymers was maximized controlling the pH, and by forming the films at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(71 citation statements)
references
References 71 publications
4
62
0
2
Order By: Relevance
“…It expresses the capability of a material to resist changes of shape without crack formation. Films intended for transdermal drug delivery must be flexible enough to follow the movements of the skin (18,22). It has been reported that an ideal transdermal film should be soft and tough that can be characterized by a high elongation value (23,24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It expresses the capability of a material to resist changes of shape without crack formation. Films intended for transdermal drug delivery must be flexible enough to follow the movements of the skin (18,22). It has been reported that an ideal transdermal film should be soft and tough that can be characterized by a high elongation value (23,24).…”
Section: Resultsmentioning
confidence: 99%
“…Elongation at break (%) indicates the flexibility of films and it has been defined as the ratio between the extension of the film at the point of rupture and the initial length of the sample (18). Elongation testing of sodium alginate-based transdermal films of DNP (TF-CONT, TF-LM1, TF-LM3, and TF-LM5) was performed using texture profile analyzer (TA-XT Plus, Stable Micro Systems, Surrey, UK) equipped with a 5-kg load cell.…”
Section: Physicochemical and Mechanical Characterization Of Dnp Transmentioning
confidence: 99%
“…The endothermic peak in CS thermogram might be related to the glass transition temperature (Tg) of Cs and the exothermic peak at 325°C was probably due to degradation of the polymer (22)(23)(24). Thermograms of nanoparticle formulations were the same and showed only a broad endothermic peak around 140 -170°C.…”
Section: Discussionmentioning
confidence: 99%
“…CB solutions (1% w/v) were prepared by dissolving in water. The pH of the solutions was adjusted at 1 by addition of 1 M HCl, in order to avoid precipitation when mixing the solutions of the polymers (13,29). Both CH and CB solutions were filtered through Miracloth® (Calbiochem-Novabiochem Corp., San Diego, CA) to remove impurities prior to use.…”
Section: Preparation Of the Filmsmentioning
confidence: 99%
“…Specifically, films based on CH have been mainly developed for food packaging (9), or for pharmaceutical applications. In the latter case, different administration routes and uses such as buccal delivery of flufenamic (10), control release of amoxicillin in stomach for the treatment of Helicobacter pylori (11), vaginal delivery of metronidazole for the treatment of bacterial vaginosis (12), or potential skin drug delivery systems (13) were evaluated. Several works have studied the mechanical properties of CH films, demonstrating that these properties may be improved when CH forms polyelectrolyte complexes with other polymers oppositely charged (14,15).…”
Section: Introductionmentioning
confidence: 99%